FOOT COMPLICATIONS IN DIABETES: A COMPREHENSIVE EXAMINATION OF QUALITY OF LIFE FROM A SPECIALIZED CLINIC’S VIEWPOINT - Hassan, Fatima Ahmed; Marcelo , da Silva Almeida; Abdel-Rahman , Mahmoud Ali (Research Journal of Health, Medicine and Nursing, 2024)
Diabetes Mellitus (DM) is a pervasive and intricate chronic condition, imposing a significant societal, economic, and human burden globally. The incidence of DM continues to rise, leading to alarming morbidity and mortality rates. Diabetic foot complications are among the most severe and costly consequences of DM. This paper highlights the importance of comprehensive assessment, preventive measures, and multidisciplinary healthcare approaches in managing diabetic foot conditions. By adopting a multiprofessional healthcare team and providing education and prevention strategies, it is possible to substantially reduce the prevalence of foot complications and amputations related to diabetes. This comprehensive approach is crucial in curbing the devastating impact of DM on patients' quality of life and the healthcare system.